1964
DOI: 10.1126/science.146.3643.535
|View full text |Cite
|
Sign up to set email alerts
|

Enolase: Multiple Molecular Forms in Fish Muscle

Abstract: Starch-gel electrophoresis shows three distinct molecular forms of enolase in each of eight different species of Salmonidae. The three enolases do not appear to be artifacts of isolation, and their electrophoretic patterns are completely reproducible. The patterns are also highly characteristic for each individual species of fish, and together with the overall myogen patterns they represent unequivocal means of taxonomical identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1966
1966
1976
1976

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Bristol. enzyme activity (Hartshorne &;Perry, 1962;Tsuyuki, 1963), parallel running of purified enzyme preparations (Tsuyuki & Wold, 1964;Scopes, 1964a) and the use of specific staining techniques (e.g. Markert & M0ller, 1959;Spencer, Hopkinson & Harris, 1964;Sjorvall & Voigt, 1964;Scopes, 1964b).…”
mentioning
confidence: 99%
“…Bristol. enzyme activity (Hartshorne &;Perry, 1962;Tsuyuki, 1963), parallel running of purified enzyme preparations (Tsuyuki & Wold, 1964;Scopes, 1964a) and the use of specific staining techniques (e.g. Markert & M0ller, 1959;Spencer, Hopkinson & Harris, 1964;Sjorvall & Voigt, 1964;Scopes, 1964b).…”
mentioning
confidence: 99%
“…The crystalline enzyme contains three electrophoretically distinct enolases, and since the same ratio of these three enzyme forms was present in the original muscle extract, it is concluded that the three forms are not artifacts of isolation. Working with the mixture of the three forms, the trout muscle enolase has been characterized with respect to physical, chemical, and bio-T A he skeletal muscle of several species of Salmonidae has been reported to contain multiple forms of the common glycolytic enzyme enolase(2-phospho-D-glycerate-hydro-lyase (4.2.1.11)) (Tsuyuki and Wold, 1964). In an attempt to investigate this phenomenon in some detail in terms of both the structural and functional significance of the different forms of enolase, a pure preparation of enolase must first be obtained.…”
mentioning
confidence: 99%
“…The protein samples were dialyzed against the electrophoresis buffer for several hours before being applied to the gel. A horizontal section of the gel was stained with amido black (Tsuyuki, 1963). For the purpose of determining which of the stained protein bands corresponded to enolase, a uniform cylinder of gel was removed from appropriate locations in the unstained counterpart of the gel with a flat, 13-gauge hypodermic needle.…”
mentioning
confidence: 99%
“…and Salmo spp. (Tsuyuki & Wold, 1964); sorbitol dehydrogenase in Salmo irideus and Coregonus lavaretus (L.) ; m-TDH in Sulmo gairdneri irideus Gibbons, 1855 ; trypsin and chymotrypsin in 0. tschawytscha (Croston, 1965); blood group antigens in 0. nerka (Ridgway, 1967) ; a glyceraldehyde phosphate dehydrogenase (Lebherz & Rutter, 1967); visual pigments in Oncorhynchus spp. (Munz & Beatty, 1965).…”
Section: Significance and Application Of Studies On Biochemical Genetmentioning
confidence: 99%